OPPORTUNITIES FOR USING ARTIFICIAL INTELLIGENCE TOOLS IN TEACHING ENGLISH AT TECHNICAL COLLEGES (Multidisciplinary Journal of Science and Technology, 2026)
The rapid development of artificial intelligence has created new pedagogical opportunities for English language teaching, especially in technical colleges where learners need both communicative competence and profession-oriented language skills. Unlike general secondary education, technical colleges require English instruction to be connected with vocational terminology, workplace communication, technical documentation, safety instructions, professional presentations, and digital literacy. This article analyzes the opportunities for using artificial intelligence tools in teaching English at technical colleges through an IMRAD-based conceptual-analytical approach. The study examines how AI-supported platforms, generative language models, automated feedback systems, speech recognition tools, machine translation, adaptive learning environments, and AI-based assessment applications can support English language learning. The analysis shows that AI tools may improve personalization, expand access to authentic language practice, support pronunciation and writing development, reduce teachers’ routine workload, and strengthen profession-oriented English instruction. However, the effective use of AI depends on methodological control, teacher competence, ethical regulation, data privacy, academic integrity, and the preservation of human interaction in the classroom. International guidance emphasizes that AI in education should be human-centred, ethically regulated, and pedagogically justified rather than used as a replacement for teachers. The article concludes that AI tools can be highly valuable in technical colleges if they are integrated into lesson objectives, vocational content, communicative tasks, and assessment criteria. The proposed model recommends using AI as a supportive didactic instrument for planning, practice, feedback, differentiation, and reflection, while maintaining the teacher’s central role in instruction, motivation, critical thinking, and ethical supervision.